Echoes of the past: niche evolution, range dynamics, and their coupling shape the distribution of species in the Chrysanthemum zawadskii species complex - Lu, Wen-Xun; Wang, Zi-Zhao; Hu, Xue-Ying; Rao, Guang-Yuan (Frontiers in Ecology and Evolution, 2023)
The distribution of species changes over time, and the current distribution of different species could result from distinct eco-evolutionary processes. Thus, investigating the spatiotemporal changes in the niche and geographic range of species is fundamental to understanding those processes and mechanisms shaping the current distributions of species. However, many studies only compared the current distribution and niche of the target species, ignoring the fact that the range shift of species is a dynamic process. Here, we reconstructed niche evolution and range dynamics of species to provide more information on related eco-evolutionary processes. We focused on a monophyletic species complex, Chrysanthemum zawadskii species complex, in which species occupy diverse habitats and exhibit different distribution patterns. Specifically, we investigated the niche breadth and overlap between lineages or species of the complex in geographic and environmental spaces. We then tested the phylogenetic signals for different climatic variables and estimated the niche of ancestral nodes on a time-calibrated phylogeny. Next, we used phyloclimatic modeling to reconstruct the dynamics of range shift for this complex. Our results show that this complex contains both specialist and generalist species, and niche diverges greatly among different species and intraspecific lineages of the complex. The moisture gradient may be the primary driver of the niche divergence of species in the complex. The reconstruction of ancestral distribution shows that this complex originated in the Qinling mountains and surrounding areas during the early Pliocene, and then diverged with the range expansion and niche evolution. Species of the complex have different range dynamics. Based on our findings, we propose that niche evolution, range dynamics, and their coupling shape the distribution of species, which provides insight into the eco-evolutionary processes that formed the current distribution of species in the C. zawadskii complex.